2022
DOI: 10.3389/fonc.2022.926437
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional, chromatin, and metabolic landscapes of LDHA inhibitor–resistant pancreatic ductal adenocarcinoma

Abstract: Metabolic reprogramming, due in part to the overexpression of metabolic enzymes, is a key hallmark of cancer cells. Lactate dehydrogenase (LDHA), a metabolic enzyme that catalyzes the interconversion of lactate and pyruvate, is overexpressed in a wide variety of cancer types, including pancreatic ductal adenocarcinoma (PDAC). Furthermore, the genetic or pharmacological inhibition of LDHA suppresses cancer growth, demonstrating a cancer-promoting role for this enzyme. Therefore, several pharmacological LDHA inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Abnormally high LDHA expression is closely related to the malignant progression of numerous types of cancer ( 40 ). Several specific inhibitors of LDHA are currently being assessed as potential anticancer treatments ( 41 ). A recent study reported that acyl phosphatase 1 (ACYP1) serves a tumour promoting role by activating the c-MYC/LDHA axis to promote glycolysis.…”
Section: Glucose Metabolic Reprogramming Affects Hccmentioning
confidence: 99%
“…Abnormally high LDHA expression is closely related to the malignant progression of numerous types of cancer ( 40 ). Several specific inhibitors of LDHA are currently being assessed as potential anticancer treatments ( 41 ). A recent study reported that acyl phosphatase 1 (ACYP1) serves a tumour promoting role by activating the c-MYC/LDHA axis to promote glycolysis.…”
Section: Glucose Metabolic Reprogramming Affects Hccmentioning
confidence: 99%
“…However, considering the ability of cancer cells to develop drug resistance, it can be assumed that they are capable of adapting to the inhibition of various branches of energy and plastic metabolism, including the inhibition of LDH [4]. Therefore, understanding the process of tumor cell adaptation is essential for optimizing the use of agents capable of inhibiting metabolic enzymes to improve treatment or prevent the development of resistance to antimetabolic therapy.…”
mentioning
confidence: 99%